On cultural studies, again. (May 2020) - Ang, Ien
This article reflects on the state of cultural studies today. It asks to what extent cultural studies can move with the times, now that we live in a radically altered world dominated by global challenges such as climate change, the rise of China, and technological transformation. It points to the importance of focusing on cultural studies' institutional and material conditions of possibility if it is to continue to exist as a distinct intellectual field.